The impact of lower extremity mass and inertia manipulation on sprint kinematics - Bennett, J. P.; Sayers, M. G. L.; Burkett, B. J. (The Journal of Strength and Conditioning Research, 2009)
Resistance sprint training is a sprint-specific training protocol commonly employed by athletes and coaches to enhance sprint performance. This research quantified the impact of lower extremity mass and inertia manipulation on key temporal and kinematic variables associated with sprint performance. A 3-dimensional analysis of 40 m sprinting was conducted on 8 elite sprinters under normal conditions and resisted sprint training. Results of the study showed that lower extremity additional mass training (at 10% individual segment weight) led to a significant reduction in sprint time for both the 10-m to 20-m and the 30-m to 40-m splits and the total 40 m measure. The stride velocity throughout the 20-m to 30-m phase of the sprint trials was also shown to be significantly reduced in the lower extremity mass and inertia manipulation condition. Importantly, no significant differences were observed across the remaining spatiotemporal variables of stride length, stride frequency, total stride time, and ground contact time. For coaches and athletes, the addition of specific lower extremity mass could improve the athlete's sprint performance without any measured effect on the technique of highly trained elite sprinters.